PENGARUH KEMANDIRIAN BELAJAR DAN KEDISIPLINAN BELAJAR TERHADAP PENGUASAAN KONSEP IPA - Fauzan, Imam (Journal of Innovation Research and Knowledge, 2023)
The Influenceof Problem Based Learning Strategy and Learning Autonomy toward Mathematics Learning Result. The Effect of Learning Independence and Learning Discipline on the Mastery of the Concept of Natural Sciences (Survey on State MTs in South Jakarta). The purpose of this study was to determine the effect of learning independence and discipline on the mastery of science concepts, the direct effect of learning independence on the mastery of science concepts, the direct influence of learning discipline on the mastery of the concepts of science and the indirect effect of learning independence and discipline on the mastery of science concepts. The research method used was a survey with Path analysis statistics, with an affordable population of all State MTs students in South Jakarta. Through a multi-stage proportional sampling technique a sample of 77 students was obtained. The type of testing used is Path using the SPSS application program. The results of the study prove that there is an effect of learning independence and learning discipline on the mastery of the Concept of Science.